2021
DOI: 10.1152/japplphysiol.00311.2020
|View full text |Cite
|
Sign up to set email alerts
|

Systemic but not local rehydration restores dehydration-induced changes in pulmonary function in healthy adults

Abstract: Water transport and local (airway) hydration are critical for the normal functioning of lungs and airways. Currently, there is uncertainty regarding the effects of systemic dehydration on pulmonary function. Our aims were: i) to clarify the impact of exercise- or fluid restriction-induced dehydration on pulmonary function in healthy adults; and ii) to establish whether systemic or local rehydration can reverse dehydration-induced alterations in pulmonary function. Ten healthy participants performed four experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…A previous study supported that systemic rehydration restores dehydration-induced changes in pulmonary function in healthy adults [51]. This study aimed to clarify the impact of exercise-induced dehydration or fluid restriction-induced dehydration on pulmonary function in healthy adults and establish whether systemic or local rehydration can reverse dehydration-induced alterations in pulmonary function.…”
Section: Effects Of Hydration On Pulmonary Functionmentioning
confidence: 70%
“…A previous study supported that systemic rehydration restores dehydration-induced changes in pulmonary function in healthy adults [51]. This study aimed to clarify the impact of exercise-induced dehydration or fluid restriction-induced dehydration on pulmonary function in healthy adults and establish whether systemic or local rehydration can reverse dehydration-induced alterations in pulmonary function.…”
Section: Effects Of Hydration On Pulmonary Functionmentioning
confidence: 70%
“…PCL thickness can be restored (or further thinned) by deposition of hypertonic (or hypotonic) saline on the surface of the ALF. Unlike the case of isotonic saline, for which deposition on the surface of ALF increases the condensation layer thickness without increasing PCL thickness and, therefore, is incapable of modulating dysfunction (Marshall et al , 2021 ), deposition of droplets of mass M D with hypertonic (or hypotonic) salt ion concentration C D may raise (or lower) the tonicity of the ALF sufficiently to hydrate (or dehydrate) the PCL by osmotic water flux from epithelial cells. This mass can be estimated by a simple mass balance.…”
Section: Resultsmentioning
confidence: 99%
“…This study has shown that ECV was lower in patients with EIB, it means that EIB is related to the dehydration of the body. A latest research (Hannah Marshall et al 2020) which has proposed that "in healthy adults: i) mild systemic dehydration induced by exercise or uid restriction leads to pulmonary function impairment, primarily localized to small airways; and ii) systemic, but not local, rehydration reverses these potentially deleterious alterations." also supported our proposal.…”
Section: Discussionmentioning
confidence: 99%